Cognitive and Self-regulation Strategies, Academic Engagement and Academic Achievement in Higher Education Students. The Mediating Role of Reading Comprehension - Arán-Filippetti, Vanessa (2023)
The aim of the present study was to examine the relationship between students’ cognitive and self-regulatory strategies, academic engagement, and academic achievement in higher education, analyzing the mediating role of reading comprehension. Different tasks to assess the constructs were administered to 209 students (Mage = 21.71; SD = 4.36). The students' GPA was used as a measure of academic achievement. Significant associations were found between cognitive and self-regulation strategies, academic engagement, reading comprehension, and students' GPA. In addition, a positive association was found between cognitive and self-regulation strategies and academic engagement. Finally, the structural equation model showed that cognitive and self-regulation strategies and academic engagement have direct effects on students' GPA. Additionally, an indirect effect of cognitive and self-regulation strategies on academic achievement was observed through reading comprehension. The implications of the study are discussed in terms of the importance of promoting the recognition and implementation of students' own cognitive and metacognitive strategies and engagement, in order to improve their academic achievement in higher education.